External and Internal Radiation Doses from Chemical Fertilisers Used in Ibadan, Oyo State, Nigeria (Global Journal of Science Frontier Research, 2018)
Absract-The knowledge of external and internal doses of radiation emitted from radionuclides contained in different chemical fertilizers sold in Ibadan, Nigeria is very important. Therefore, activity concentrations of 40K, 226Ra and 232Th radionuclides in Urea, NPK (15 -15 -15), NPK (16 -16 -16) and Single Super Phosphate (SSP) fertilizer brands sold in the area for agricultural purposes were determined using gamma-ray spectroscopy. Radium equivalent activity (Raeq), gamma radiation or representative index ( ), alpha index ( ), annual gonadal dose equivalent (AGDE), external exposure (D ext ) to gamma radiation as well as internal exposure (D int ) to doses of radiation to the marketers and users of the products were calculated. The calculated Ra eq for the four brands of chemical fertilizers were 80.90 , 295.95 , 293.93 and 706.17 respectively. External gamma doses were 0.60 6.73 , 6.65 and 13.00 while the sum of the internal doses due to inhalation and ingestion were found as 3.93 , 4.51 , 3.61 and 8.97 respectively. More external and internal doses of radiation were calculated for marketers of the products than farmers.
Keywords: chemical fertilizers; ionizing radiation; external exposure; somatic effects; radium equivalent activity